Cell-cycle arrest induced by the bacterial adenylate cyclase toxins from Bacillus anthracis and Bordetella pertussis - Gray, Mary C. (2010)
Bacillus anthracis Edema Toxin (ET) and Bordetella pertussis Adenylate Cyclase Toxin (ACT) enter host cells and produce cAMP. To understand the cellular consequences, we exposed J774 cells to these toxins at ng/ml (pM) concentrations, then followed cell number and changes in cell signaling pathways. Under these conditions, both toxins produce a concentration-dependent inhibition of cell proliferation without cytotoxicity. ET and ACT increase the proportion of cells in G(1)/G(0) and reduce S-phase, such that a single addition of ET or ACT inhibits cell division for 3 to 6 days. Treatment with ET or ACT produces striking changes in proteins controlling cell cycle, including virtual elimination of phosphorylated ERK 1/2 and Cyclin D1 and increases in phospho-CREB and p27(Kip1). Importantly, PD98059, a MEK inhibitor, elicits a comparable reduction in Cyclin D1 to that produced by the toxins and blocks proliferation. These data show that non-lethal concentrations of ET and ACT impose a prolonged block on the proliferation of J774 cells by impairment of the progression from G(1)/G(0) to S-phase in a process involving cAMP-mediated increases in phospho-CREB and p27(Kip1) and reductions in phospho-ERK 1/2 and Cyclin D1. This phenomenon represents a new mechanism by which these toxins affect host cells.